Hadrons, nuclei, and applications : proceedings of the conference, Bologna 2000, structure of the nucleus at the dawn of the century : Bologna, Italy, 29 May-3 June 2000 - Bonsignori, Giovanni C. (Science and culture series (Singapore). Advanced scientific culture, 2001)
The Conference "Bologna 2000: Structure of the Nucleus at the Dawn of the Century" was devoted to a discipline which has seen a strong revival of research activities in the last decade. New experimental results and theoretical developments in nuclear physics will certainly make important contributions to our knowledge and understanding of Nature's fundamental building blocks. The interest aroused by the Conference among the scientific community was clearly reflected in the large number of participants. These represented the most important nuclear physics laboratories in the world. The Conference covered five major topics of modern nuclear physics: nuclear structure, nucleus-nucleus collisions, hadron dynamics, nuclear astrophysics, and transdisciplinary and peaceful applications of nuclear science. It reviewed recent progress in the field and provided a forum for the discussion of current and future research projects.